Do Workers' Remittances Reduce The Probability of Current Account Reversals ? - Bugamelli, Matteo (The World Bank, 2005)
The authors combine the literature on financial crises in emerging markets and developing economies with that on international migrations by investigating whether the increasingly large flows of workers' remittances can help reduce the probability of current account reversals. The rationale for this stands in the great stability and low cyclicality of remittances as compared with other private capital flows: these properties, combined with the fact that remittances are cheap inflows of foreign currencies, might reduce the probability that foreign investors suddenly flee out of emerging markets and developing economies and trigger a dramatic current account adjustment. The authors find that remittances can have such a beneficial effect. In particular, they show that a high level of remittances, as a ratio of GDP, makes the relationship between a decreasing stock of international reserves (over GDP) and a higher probability of current account crises less stringent. The same occurs, though less neatly, for the positive relationship between an increasing stock of external debt (over GDP) and the probability of current account reversals. The results point also to a threshold effect of remittances: the mechanisms just described are, in fact, much stronger when remittances are above 3 percent of GDP